CHANGES IN THE HISTORICAL PROCESS OF THE MUNICIPALITY LAW AND THE INVESTIGATION OF THE LAW NO 6360 - Duygu AKYOL (Fırat University, 2019)
Turkey also all arrangements associated with metropolitan municipality is based on the 1982 Constitution. Within the changing world order, the needs of the cities are increasing day by day and various regulations are being made in the metropolitan municipality in order to respond to these needs. One of the drawbacks of these regulations was the Law No. 6360. Radicals contained in the law and the facilities provided by the cities to become major cities are striking. Law No. 6360, issued in December 2012 and making significant changes in local government legislation, has taken its place on the agenda by adding a new dimension to the discussions of municipalities on scale. In practice, administrative, political, social and urban effects of the new metropolitan model, which started to be implemented after the 2014 local elections, have begun to be seen. In this study, primarily the historical development of the metropolitan management system within the Turkish local government system will be outlined. Then, by determining the characteristics of the new metropolitan city system, we will examine how the cities will change with the law and what the city expects, and the current situation and advantages and disadvantages will be revealed.